Legal Regulation of Alternative Sanctions: The Jordanian Experience - Al-Zoubi , Muath Yahya (Dirasat: Shari'a and Law Sciences, 2020)
This paper deals with the legal regulation of alternative sanctions by shedding light on the Jordanian experience in this regard through addressing three main issues: the nature of alternative sanctions, the forms of alternative sanctions and the alternatives to community reform as an effective alternative to the original sanction. This research uses a critical analytical approach so that this approach serves to determine the method of law enforcement on the issues that have been touched upon in the field of Alternative Sanctions. In addition, the descriptive approach was used by showing what the situation is in the field of Alternative Sanctions, and how alternative sanctions have been dealt with from a legal point of view. Finally, the comparative approach was used, where different situations, cases, and legal systems were compared on issues related to the topic of Alternative Sanctions. This paper illustrates that the alternative sanctions are based on the idea that the original sanctions should be replaced by alternative sanctions under specific conditions and grounds; in order to avoid the shortcomings of the practical application of short-term sanctions. The study recommended the need to benefit from the experiences of some leading countries in the field of applying alternative sanctions, and the use of some model laws that addressed the subject of Alternative Sanctions.